Structural Drivers of Wage Inequality: An Analysis of Minimum Wage Policy Impact on Thai and CLM Migrant Workers - WIN, SANN NAING (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The declining working-age population of Thailand’s labor force relies on both Thai and large numbers of migrant workers from Cambodia, Laos, and Myanmar (CLM), who are disproportionately absorbed into both the formal and informal sectors, specifically into low-wage, unstable jobs with weak enforcement and vulnerable employment conditions. The study aims to examine the impact of changes to the minimum wage policy on the wages of Thai and CLM workers in the formal and informal sectors. The analysis uses minimum wage data and cross-sectional, pooled third-quarter data from the Thailand Labor Force Survey (2023-2024). It focuses on private-sector employees, who represent most Thai and CLM workers. This research employs continuous difference-in-differences to identify how changes in the minimum wage policy affect Thai and CLM differently before (2023) and after (2024). The result indicates that the wage distribution appears to improve wages for both Thai and CLM workers following the policy changes. The continuous difference-in-differences result shows that a 1-percentage-point growth in minimum wage significantly reduces the hourly wage response in the formal sector by approximately 3.16% for CLM workers relative to Thai workers. Otherwise, a 1-percentage-point growth in minimum wage significantly increases the hourly wage response by approximately 1.93% for CLM workers compared to Thai workers in the informal sector. Overall, the findings indicate the existing vulnerability of CLM workers and enforcement gaps that continue to hinder the transmission of wage outcomes across sectors, suggesting expanding the social security fund coverage and strengthening law enforcement and compliance in the Thai labor market.